2017
DOI: 10.1038/srep45104
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hexose kinase genes in Kluyveromyces marxianus and thermo-tolerant one step producing glucose-free fructose strain construction

Abstract: In yeast, the hexose assimilation is started at hexose phosphorylation. However, in Kluyveromyces marxianus, the hexokinase (HXK) and glucokinase (GLK) genes were not identified by experiments. Meanwhile, the glucose-free fructose product requires more cost-efficient method. In this study, the KmHXK1 and KmGLK1 genes were functionally identified through gene disruption, over-expression and recombinant enzymes characterization. Both glucose and fructose assimilation ability decreased significantly in KmHXK1 dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…1a) [21, 22]. However, only one HXK and one GLK were identified in K. marxianus in our previous study [17]. For this reason, KmHXK1 and KmGLK1 were selected for investigation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1a) [21, 22]. However, only one HXK and one GLK were identified in K. marxianus in our previous study [17]. For this reason, KmHXK1 and KmGLK1 were selected for investigation.…”
Section: Resultsmentioning
confidence: 99%
“…It indicated that Km HXK1, the only hexokinase in K. marxianus [17], can generate glucose repression-related signals and its disruption released the utilization of xylose and other nonglucose sugars from glucose repression. On the other hand, the disruption of KmGLK1 which is nonessential for hexose phosphorylation in K. marxianus [17] did not cause any phenotypic change.
Fig. 1The putative pathway and analysis schematic diagram of glucose repression in K. marxianus.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hexokinase gene RAG5 in strain M2 had more than twofold up-regulation compared with that in control strain, while the glucokinase gene GLK1 was slightly down-regulated. Considering that the hexokinase of K. marxianus can phosphorylate both glucose and fructose [ 39 ], the up-regulation of RAG5 in strain M2 might promote its glucose assimilation ability. The glucose-6-phosphate dehydrogenase gene ZWF was down-regulated in strain M2, which might decrease the carbon flux through the pentose phosphate pathway (PPP) [ 40 ].…”
Section: Resultsmentioning
confidence: 99%